Application of the Layered Learning Practice Model in an Academic Medical Center. Issue 4 (April 2017) - Loy, Brittany M.; Yang, Sendra; Moss, Jason M.; Kemp, Debra W.; Brown, Jamie N.
The layered learning practice model (LLPM) is a teaching strategy designed to train residents to precept students and other residents with the oversight of a seasoned clinical pharmacist. This model serves as a tool for residency programs to implement quality precepting opportunities and learning experiences as they look for new ways to integrate multiple learners into the practice setting. The levels of the LLPM include a senior preceptor, resident, and student. It is best implemented through utilization of 4 steps: orientation to the LLPM, preexperience planning, implementation, and postexperience evaluation. Orientation introduces preceptors and residents to the LLPM and outlines expectations for each precepting level. Preexperience planning allows the resident to take a leadership role in developing calendars, rotation activities, rubrics, and activities that match goals and objectives. For implementation, the senior preceptor maintains an active role with all learners; the resident serves as the student's primary preceptor and is responsible for incorporating the student into clinical activities, evaluating student work, and providing feedback. Postexperience evaluation is designed to solicit and provide feedback to the resident and student and to identify recommendations for improvement of the LLPM. Overall, the LLPM is a multi-layered model incorporating the expertise and unique learning positions of the senior preceptor, resident, and student. Redistributing components of the senior preceptor's responsibility amongst learners may result in expansion of patient care and clinical services and help satisfy the increasing demands placed on pharmacists.